2020
DOI: 10.1002/14651858.cd013226.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony stimulating factor administration for subfertile women undergoing assisted reproduction

Abstract: Granulocyte-colony stimulating factor administration for subfertile women undergoing assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…However, neither the clinical pregnancy rate nor the live birth rate increased in an RCT including 157 RIF patients reported by Kalem [ 17 ]. Recently, in a meta-analysis that included 1253 infertile women, Kamath et al reported no difference between the G-CSF group and the control group [ 18 ]. However, their target population was all infertile women undergoing ART instead of only RIF patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, neither the clinical pregnancy rate nor the live birth rate increased in an RCT including 157 RIF patients reported by Kalem [ 17 ]. Recently, in a meta-analysis that included 1253 infertile women, Kamath et al reported no difference between the G-CSF group and the control group [ 18 ]. However, their target population was all infertile women undergoing ART instead of only RIF patients.…”
Section: Introductionmentioning
confidence: 99%
“…So far 10 randomized controlled trials have been published (Barad et al, 2014;Aleyasin et al, 2016;Davari-Tanha et al, 2016;Eftekhar et al, 2016a,b;Sarvi et al, 2017;Arefi et al, 2018;Bakirarar et al, 2018;Huang et al, 2020a;Kalem et al, 2020), with conflicting results, followed by meta-analyses in a timely manner (presented in Table 5). The six meta-analyses published present rather supportive results (Zhao et al, 2016;Kamath et al, 2017;Li et al, 2017a;Hou et al, 2018;Jiang et al, 2020;Kamath et al, 2020). However, most of the meta-analyses have included both randomized controlled trials and non-randomized trials, weakening the level of evidence.…”
Section: Granulocyte Colony Stimulating Factor (G-csf)mentioning
confidence: 97%
“…However, most of the meta-analyses have included both randomized controlled trials and non-randomized trials, weakening the level of evidence. The most powered meta-analysis at the moment is a Cochrane review including 15 randomized control trials with 1,253 participants ( Kamath et al, 2020 ). The authors have shown a weak positive impact of G-CSF in reproductive outcomes, advising caution due to low quality data and increased uncertainty.…”
Section: Approaches To Improve Endometrial Receptivity In Unexplainedmentioning
confidence: 99%
See 1 more Smart Citation
“…Granulocyte colony-stimulating factor (G-CSF) is secreted by multiple cells including macrophages ( 67 , 68 ) and placental villous trophoblasts ( 69 ). Increasing evidence demonstrates the therapeutic effect of G-CSF in RSA, repeated implantation failure, luteinized unruptured follicle syndrome and women with thin endometrium ( 70 72 ). Previously, by using a co-cultured model, our study showed that trophoblasts-derived IL-6 promoted M2 macrophage polarization ( 73 ), which in turn induced the epithelial-mesenchymal transition of trophoblasts, thereby promoting migration and invasion though secreting G-CSF to activate PI3K/AKT/Erk1/2 signaling pathway ( 68 ).…”
Section: Crosstalk Between Trophoblasts and Macrophages At The Maternal-fetal Interfacementioning
confidence: 99%